Simulation and Analysis of the Optimal Electric Field from Modifications to the Winding Design for the Tesla Transformer - Nattachote Rugthaicharoencheep; Supawud Nedphokaew (Energies)
This research aims to present a study of the effects of the Tesla transformer in order to find the proper dimensions. We created a design of the Tesla transformer to reduce the high-voltage electric field-stress problem that happens between primary winding and secondary winding. Because the Tesla transformer is used to induce voltage between these two windings through the air, problems with insulation occur. The winding that has space is dielectric; while there is high voltage in a transformer, it causes flashover voltage between the high-voltage winding and low-voltage winding, which damages the transformer and other devices. Research process: Research was conducted to study the laydown model (positioning) of the two windings in the transformer. By considering this, we induced a proper Tesla transformer that was reproduced by using the FEMLAB program. Moreover, we compared the Tesla transformer reproduction, which created a voltage of 120 kV and a frequency of 120 kHz. The result from the comparison is a proper laydown position of the primary winding and voltage, which has been designed without the flashover. The whorl coil has to be wound at a 60-degree angle relative to the floor and can induce more voltage than other models. The voltage and corresponding electric field stress were measured for the primary winding at various angles relative to the floor (0-, 30-, 45-, 60-, and 90-degree angles) to determine the configuration. The results from the reproduction using the FEMLAB program and testing demonstrated that no flashover occurred between the high-voltage winding to the low-voltage winding when the primary winding was positioned at a 60-degree angle.